Ebony & ivy : race, slavery, and the troubled history of America's universities - Wilder, Craig Steven (Bloomsbury Press, 2013)
A leading African American historian of race in America exposes the uncomfortable truths about race, slavery, and the American academy, revealing that leading universities, dependent on human bondage, became breeding grounds for the racist ideas that sustained it.